Analysis of sugar components and identification of SPS genes in citrus fruit development - Lu, Wen; Hao, Wenhui; Liu, Kexin; Liu, Jiahuan; Yin, Chunmei; Su, Yujiao; Hang, Zhiyu; Peng, Bin; Liu, Huan; Xiong, Bo; Liao, Ling; He, Jiaxian; et al. (Frontiers in Plant Science, 2024)
Sugar is a primary determinant of citrus fruit flavour, but undergoes varied accumulation processes across different citrus varieties owing to high genetic variability. Sucrose phosphate synthase (SPS), a key enzyme in glucose metabolism, plays a crucial role in this context. Despite its significance, there is limited research on sugar component quality and the expression and regulatory prediction of SPS genes during citrus fruit development. Therefore, we analysed the sugar quality formation process in 'Kiyomi' and 'Succosa', two citrus varieties, and performed a comprehensive genomewide analysis of citrus CsSPSs. We observed that the accumulation of sugar components significantly differs between the two varieties, with the identification of four CsSPSs in citrus. CsSPS sequences were highly conserved, featuring typical SPS protein domains. Expression analysis revealed a positive correlation between CsSPS expression and sugar accumulation in citrus fruits. However, CsSPS expression displays specificity to different citrus tissues and varieties. Transcriptome coexpression network analysis suggests the involvement of multiple transcription factors in shaping citrus fruit sugar quality through the regulation of CsSPSs. Notably, the expression levels of four CsWRKYs (CsWRKY2, CsWRKY20, CsWRKY28, CsWRKY32,) were significantly positively correlated with CsSPSs and CsWRKY20 might can activate sugar accumulation in citrus fruit through CsSPS2. Collectively, we further emphasize the potential importance of CsWRKYs in citrus sugar metabolism, our findings serve as a reference for understanding sugar component formation and predicting CsSPS expression and regulation during citrus fruit development.